The behavior of chemical compositions in the snow and atmosphere on the Mizuho Plateau - Satoru Kanamori; Nobuko Kanamori; Okitsugu Watanabe; Masataka Nishikawa; Kokichi Kamiyama; Hideaki Motoyama (National Institute of Polar Research, 1997)
Atmospheric aerosols were studied at Syowa Station, Antarctica for 3 years from 1988 to 1990. Some chemical species, such as exSO_4^, MSA and NH_4^+, showed an annual trend, high in summer and low in winter. The seasonal variations of gaseous HCl, SO_2,HNO_2,HNO_3 were also studied and the occurrence of very high HCl gas in summer and the comparable concentrations of others gases to those of aerosols were found. The size distribution of aerosol particles over inland area and marine water were measured. The particle radius at the concentration maximum of exSO_4^ as well as MSA were found at 0.35μm, indicating secondary particles production from gases. In most case, atmospheric aerosols had negative exCl^- value showing Cl^- defect as compared to Na^+. From the observation at 5 snow pits on the Mizuho Plateau, apparent seasonal variations in δ^O, Cl^- and Na^+ were found only at the 2 inland points. From the drifting snow studies, Cl^-, Na^+, exSO_4^, NO_3^- and MSA showed the distribution of high in sea-side and low in inland and then re-increase in the inner area indicating supply from inland. Most snow samples showed positive exCl^- values. A rough linear relationship among concentrations in chemical species was found between atmospheric aerosols and corresponding snow on the Mizuho Plateau and, therefore, the concentration in the aerosol is roughly reflected in the snow composition. However, the supply of chemical substances to snow from other sources than ground-level aerosols would be needed to account for the fact that some chemical items such as exCl^-, Ca^ and K^+ apparently do not satisfy the above linear relation.